Dispersion of electromagnetic waves in coaxial cylindrical rippled-wall waveguide including plasma layer - Asadiamiri, F.; Chaudhary, K.; Ali, J.; Bahadoran, M.; Nejati, Malihe; Yupapin, P. P.; Niknam, A. R. (My University, 2022)
Electronic technologies, especially in the microwave and terahertz frequency ranges, including plasma show better interaction efficiency and higher output power as compared to apparatus with the vacuum. Also, in these frequency ranges, the plasma-filled high-power waveguides can support TE and TM modes. Therefore, in this study, the dispersion relation of electromagnetic (EM) waves in a new rippled-wall waveguide structure contain the plasma layer and coaxial dielectric geometry is numerically studied. The Maxwell equations and boundary conditions are employed to investigate and analyze the dispersion relation in TM mode for coaxial geometry dielectric rippled-wall waveguide contain the plasma layer. High-frequency radiations are observed from the proposed configuration. It is found that the frequency of the wave increases with a decrease in the corrugation amplitude and period. Moreover, a decrease in frequency is observed with an increase in dielectric radius and a decrease in plasma radius.
Keywords: Dispersion relation; Maxwell equation; plasma layer; rippled-wall waveguide